The oral-gut axis in chronic atrophic gastritis: current perspectives and integrated strategies - Zha, Tianyue; Ding, Yonggang; Xu, Xingli; Zhang, Yifan; Guo, Jinwei; Ge, Huinan; Xu, Luzhou (Frontiers in Immunology, 2026)
Chronic atrophic gastritis (CAG) is a key precursor to gastric cancer, characterized by progressive mucosal atrophy, inflammation, and microbial dysbiosis. The Correa cascade model highlights Helicobacter pylori as a primary driver, progressing from gastritis to atrophy, intestinal metaplasia (IM), dysplasia, and malignancy. However, 20%–30% of CAG cases lack H. pylori involvement, emphasizing the roles of non-H. pylori microbial dysbiosis, environmental factors, and the oral-gut axis in disease progression. Oral microbes, such as Porphyromonas gingivalis, translocate to the stomach, amplifying inflammation through NF-κB and Wnt/β-catenin pathways and altering metabolites like short-chain fatty acids and trimethylamine N-oxide. Pro-inflammatory cytokines, including IL-1β, IL-6, and IL-17, alongside Th17-driven immune dysregulation, further accelerate carcinogenesis. This perspective integrates multi-omics data to elucidate microbiome shifts, metabolic changes, and immune responses across CAG subtypes. Advanced diagnostics, such as endoscopic imaging, serum biomarkers, and oral microbiota profiling, enable precise risk stratification. Management strategies extend beyond H. pylori eradication to include probiotics, fecal microbiota transplantation, periodontal interventions, and herbal compounds, targeting the oral-gut axis to restore microbial balance and halt carcinogenesis. This framework offers novel avenues for prevention and therapy in high-burden regions.